2022
DOI: 10.3390/curroncol29120736
|View full text |Cite
|
Sign up to set email alerts
|

Subaxillary Replacement Flap Compared with the Round Block Displacement Technique in Oncoplastic Breast Conserving Surgery: Functional Outcomes of a Feasible One Stage Reconstruction

Abstract: Background: For selected women diagnosed with breast cancer (BC), partial reconstructive techniques involve displacement or replacement procedures to improve cosmesis without compromising oncological safety. This study aims to evaluate the surgical outcomes of the round block (RB) compared with the subaxillary flap (SF) technique for patients with upper outer tumor. Patients and Methods: Thirty-three patients treated with oncoplastic conserving surgery (15 RB and 18 SF) were enrolled in this retrospective stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
1
0
0
Order By: Relevance
“…This study found that the excellent rate of breast cosmetic effect after BCS group was significantly higher than that of the MRM group ( p < 0.001), indicating that BCS group can fully preserve the patient's ipsilateral skin, guaranteeing the aesthetic appearance of the breast and effectively meeting the patient's requirements for physical appearance. This is consistent with previous research findings 30 …”
Section: Discussionsupporting
confidence: 94%
“…This study found that the excellent rate of breast cosmetic effect after BCS group was significantly higher than that of the MRM group ( p < 0.001), indicating that BCS group can fully preserve the patient's ipsilateral skin, guaranteeing the aesthetic appearance of the breast and effectively meeting the patient's requirements for physical appearance. This is consistent with previous research findings 30 …”
Section: Discussionsupporting
confidence: 94%